Analysis of thermal comfort on planes. Issue 1 (1st September 2022) - Krawczyk, N
Abstract: Thermal comfort of passengers and cabin crew is an important element to be ensured during short and long distance flights. The analysis of this phenomenon is usually conducted based on the measurements of physical parameters of the inside air and factors such as metabolic rate and thermal insulation of clothes. The paper provides an insight into this phenomenon through the literature review on the subject. It presents the assessment of thermal comfort conditions onboard the planes. An important element is the discussion of the current model of thermal comfort proposed by O. Fanger and its usability for the application in planes.